2017
DOI: 10.1016/j.tjog.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The association of enchondromatosis with malignant transformed chondrosarcoma and ovarian juvenile granulosa cell tumor (Ollier disease)

Abstract: It is important to recognize that when the female patient presents with enchondromatosis and a large unilateral multilocular-solid ovarian mass, the specific diagnosis of granulosa cell tumor can be made with high accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Vascular anomalies were most commonly found in the upper extremity, followed by lower extremity and axial skeleton. While vascular anomalies in MS are known to affect the meninges, tongue and oral mucosa, few case reports in the literature describe visceral organ involvement (Beltrami et al, ; Burgetova et al, ). In our literature review, we found that 15.8% of vascular anomalies were in visceral organs, and, surprisingly, the visceral vascular anomalies were found despite the absence of any visible cutaneous lesions in four patients (2.3%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular anomalies were most commonly found in the upper extremity, followed by lower extremity and axial skeleton. While vascular anomalies in MS are known to affect the meninges, tongue and oral mucosa, few case reports in the literature describe visceral organ involvement (Beltrami et al, ; Burgetova et al, ). In our literature review, we found that 15.8% of vascular anomalies were in visceral organs, and, surprisingly, the visceral vascular anomalies were found despite the absence of any visible cutaneous lesions in four patients (2.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Gonadal neoplasms, specifically juvenile granulosa cell tumor, have also been associated with OD and MS. A literature review by Pansuriya et al () found seven cases of juvenile granulosa cell tumor in patients with OD, and six cases in patients with MS. In 2017, Burgetova et al () described 10 cases of juvenile granulosa cell tumor in patients with OD. Our literature review found a slightly higher prevalence of gonadal malignancies in OD compared to MS (8.1%—OD, 3.5%—MS; p = .059).…”
Section: Discussionmentioning
confidence: 99%
“…33,34 In addition, both Ollier disease and Maffucci syndrome have been associated with the development of other tumor types, such as ovarian juvenile granulosa cell tumors. 2,35 Metachondromatosis is an inherited autosomal dominant disease caused by loss of function mutations in the PTPN11 gene. 36 Patients with metachondromatosis present early with the development of numerous enchondromas as well as osteochondromas.…”
Section: Enchondromatosismentioning
confidence: 99%
“…Tamimi and colleagues reported the first case of an ovarian JGCT in a 15-year-old girl with Ollier disease 6. Since then, 11 cases have been reported in the English literature 7. Ollier disease (OMIM #166000) and Maffucci syndrome (OMIM #614569) are skeletal disorders secondary to a dysplastic mesodermal process affecting the metaphyseal region of the short and long tubular bones.…”
Section: Sex Cord-stromal Tumours (Scst)mentioning
confidence: 99%